大豆异黄酮作为大豆溯源特征指标的筛选Screening of soybean isoflavone as characteristic index of soybean traceability - 费洪立1,2,3，阮长青1,2,3，李志江1,2,3，鹿保鑫1,2,3，张东杰1,2,3 FEI Hongli1,2,3, RUAN Changqing1,2,3,LI Zhijiang1,2,3, LU Baoxin1,2,3,ZHANG Dongjie1,2,3 (Zhongguo youzhi, 2022)
采用高效液相色谱法对黑龙江省不同产地、不同品种大豆中大豆异黄酮含量进行测定,利用不同品种和产地大豆中大豆异黄酮单体含量的不同对大豆异黄酮溯源特征指标进行筛选。结果表明:同一产地不同品种之间大豆异黄酮单体含量总体差异显著(p<0.05)，不同产地不同品种之间大豆异黄酮单体含量总体没有显著差异(p>0.05)。因此，可以利用不同品种大豆中大豆异黄酮单体含量作为对大豆异黄酮溯源特征指标实现品种溯源。 The content of soybean isoflavone in soybean from different producing areas and varieties in Heilongjiang province was detected by HPLC, and the traceability index of soybean isoflavone was screened by using the difference of soybean isoflavone monomer content in varieties and producing areas. The results showed that generally, the content of soybean isoflavone monomer was significantly different among soybean from different varieties in the same area(p<0.05), but there was no significant difference in the content of soybean isoflavone monomer among soybean from different varieties in different areas(p>0.05). Therefore, the content of soybean isoflavone monomer in different varieties of soybean could be used as the characteristic index of soybean isoflavone traceability.